The Role of Tarekat Qadiriyah wa Naqsyabandiyah in the Era of Covid-19 Pandemic - Munandar, Siswoyo Aris (UIN Sunan Kalijaga Yogyakarta, 2021)
The Covid-19 pandemic that has occurred in almost all countries, especially in Indonesia, has had a fairly severe impact on all walk of life. In this context, philanthropic actions have continued to develop; more and more companies and individuals have recently been active in philanthropic activities. This study examines the philanthropic activity of the members of the Tarekat Qadiriyah wa Naqsyabandiyah during the pandemic crisis with the help of the advanced of digital technology. It describes a movement from women follower of Tarekat Qadiriyah wa Naqysabandiyah to help people affected by Covid-19. This research shows that the tarekat movement also takes advantage of the digital technology for their philantrophic cause.